2022
DOI: 10.1002/ana.26306
|View full text |Cite
|
Sign up to set email alerts
|

Cortical Correlates of Gait Compensation Strategies in Parkinson Disease

Abstract: Objective Gait impairment in persons with Parkinson disease is common and debilitating. Compensation strategies (eg, external cues) are an essential part of rehabilitation, but their underlying mechanisms remain unclear. Using electroencephalography (EEG), we explored the cortical correlates of 3 categories of strategies: external cueing, internal cueing, and action observation. Methods Eighteen participants with Parkinson disease and gait impairment were included. We recorded 126‐channel EEG during both stanc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
20
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 30 publications
(25 citation statements)
references
References 60 publications
5
20
0
Order By: Relevance
“…These results provide evidence for the notion that application of a cognitive movement strategy poses attentional demands. Furthermore, this finding strengthens recent reports that indicated that different cortical mechanisms underlie external cueing and cognitive movement compensatory strategies ( Stuart and Mancini, 2020 ; Tosserams et al, 2022 ).…”
Section: Discussionsupporting
confidence: 90%
“…These results provide evidence for the notion that application of a cognitive movement strategy poses attentional demands. Furthermore, this finding strengthens recent reports that indicated that different cortical mechanisms underlie external cueing and cognitive movement compensatory strategies ( Stuart and Mancini, 2020 ; Tosserams et al, 2022 ).…”
Section: Discussionsupporting
confidence: 90%
“…Only the gamma band power of the parieto-occipital region decreased in non-responders. These findings support the results of previous interventions for PD showing that transcranial alternating current stimulation (tACS) (Del Felic et al, 2019) and the use of gait compensation strategies (Tosserams et al, 2022) to improve PD motor symptoms were closely related to decreased beta oscillation.…”
Section: Discussionsupporting
confidence: 88%
“…Adequate gait control therefore not only relies on the integrity and function of corticostriatal motor loops, but on compensatory input from cognitive, sensory and limbic systems as well (Fig. 2 ) [ 47 50 ]. Reinforcing the integration of these different neural networks may consequently facilitate optimal compensation for the PD-related loss of function in the motor circuitries.…”
Section: Discussionmentioning
confidence: 99%